2011
DOI: 10.1002/ajmg.c.30306
|View full text |Cite
|
Sign up to set email alerts
|

Influencing clinical practice regarding the use of antiepileptic medications during pregnancy: Modeling the potential impact on the prevalences of spina bifida and cleft palate in the United States

Abstract: Selected antiepileptic drugs (AEDs) increase the risk of birth defects. To assess the impact of influencing AED prescribing practices on spina bifida and cleft palate we searched the literature for estimates of the association between valproic acid or carbamazepine use during pregnancy and these defects and summarized the associations using meta-analyses. We estimated distributions of the prevalence of valproic acid and carbamazepine use among women of childbearing age based on analyses of four data sets. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 99 publications
0
30
0
Order By: Relevance
“…Existing research has demonstrated increasing off-label use of atypical antipsychotics and anticonvulsant medications in the U.S. and case control studies suggest that early fetal exposure to anticonvulsants may be associated with increased risk for birth defects. 412 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research has demonstrated increasing off-label use of atypical antipsychotics and anticonvulsant medications in the U.S. and case control studies suggest that early fetal exposure to anticonvulsants may be associated with increased risk for birth defects. 412 …”
Section: Discussionmentioning
confidence: 99%
“…1315 At the same time, pregnancy-related exposure to certain antipsychotics, anticonvulsants and/or lithium may place the developing fetus at risk for birth defects and other adverse outcomes. 11,12,1620 …”
Section: Introductionmentioning
confidence: 99%
“…The US Food and Drug Administration has made valproic acid a class X drug for migraines, where the risks involved in using valproic acid in pregnant women clearly outweigh potential benefits. Within the USA, it was estimated that w40 cases of spina bifida have occurred due to valproic acid use [90], and about 4 per 1000 prescriptions are still written for valproic acid for nonepilepsy conditions [89]. The March of Dimes Global report on birth defects (2006) indicated that the risk of such exposure is even higher in developing countries where valproic acid use may be uncontrolled and more common compared with more expensive and less teratogenic anticonvulsive drugs [1,91].…”
Section: Valproic Acidmentioning
confidence: 99%
“…Simulations have been used to estimate the number of cases of specific birth defects that could be prevented with decreased use of teratogenic antiepileptic medications [93]; a reduction in the prevalence of prepregnancy obesity [94]; elimination of periconceptional cigarette smoking [95]; addition of folic acid to birth control pills [96] and folic acid fortification of corn masa flour [97]. …”
Section: Challenges In Translationmentioning
confidence: 99%